Development of a Comprehensive Approach to Assessing the Content of Elemental Contaminants in Native Herbal Medicinal Products, Using Pumpkin Seeds as a Case Study - S. V. Ovsienko; N. E. Kuz'mina; V. M. Shchukin; E. A. Khorolskaya (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Native herbal medicinal products (NHMPs) are medicinal products derived from plant raw materials. NHMPs are characterised by a complete transfer of contaminants from raw materials to finished products and comparability of therapeutic doses to daily consumption of many foods. The aim of the study was to develop an approach to assessing the content of elemental contaminants in NHMPs, based on public health risk assessment methods, and exemplify its use by applying it to pumpkin seeds. Materials and methods: the study analysed national and international regulatory documents governing the control of elemental contaminants in medicinal products and food, as well as literature on the ability of pumpkin seeds to accumulate such contaminants. In order to determine permitted concentrations, hazard quotients and cancer slope factors, the authors used internationally accepted risk assessment criteria. Results: the study identified the elemental contaminants to be controlled during risk assessment of NHMPs (i.e., As, Cd, Co, Cr, Pb, Hg, Ni, and V). The authors calculated permitted concentrations of the elements for a therapeutic dose of pumpkin seeds; hazard quotients for the essential (Co, Cr, Cu, Fe, Mn, Mo, Se, Zn), probably essential (As, Ni, V) and toxic (Al, Cd, Hg, Pb, Sr, Tl) elements consumed with the dose; and individual cancer risks associated with As, Cd, Cr, Pb. Conclusions: the total health impact of the studied elements in a therapeutic dose of pumpkin seeds is permissible, and there is no risk of non-carcinogenic effects. The content of each carcinogenic element in pumpkin seeds corresponds to the acceptable level of maximum individual cancer risk. These risk levels are to be controlled at all times. The results of this study may support the development of a compendial monograph on pumpkin seeds.